Employability Pathways in Tertiary Education: Insights from Cambodian Undergraduates - Long Bunteng (Srawung: Journal of Social Sciences and Humanities, 2026)
This study investigates the institutional factors that influence students' perceptions of their employability in higher education institutions in Cambodia. A structured questionnaire disseminated over social media sites like Telegram and Messenger was used to gather data for a quantitative study design. A non-probability sampling strategy that included quota, convenience, and purposive sampling was used to guarantee representation among student cohorts and academic disciplines. Using a five-point Likert scale ranging from "Strongly Disagree" to "Strongly Agree," respondents scored their perceptions. AMOS, SPSS, JASP, and structured excel based reliability and validity calculator were used to analyze 265 valid responses to check the reliability, vcalidity, relationship and significant impacts between each variable, including curriculum relevance, personal planning development, career development learning, work experience, extra-corricular activities, exposure to real world activites, and students’ employability. The findings show that local colleges have a significant impact on graduate workforce readiness by identifying critical pathways linking institutional practices to students' employability. The study offers practical recommendations for institutional leaders and policymakers to enhance curriculum design, strengthen student support mechanisms, and foster employability-focused strategies within Cambodian higher education. These insights contribute to ongoing efforts to improve educational outcomes and align institutional practices with the evolving demands of the national workforce.